Teaching Uzbek Lexicology And Phraseology Through Semantic Analysis And Contextual Interpretation Methods - Muxanova Muyasar Gayratovna (Genius Journals, 2026)
This study examines effective methodological approaches to teaching Uzbek lexicology and phraseology through semantic analysis and contextual interpretation methods. The research focuses on the role of word meaning, semantic relationships, and phraseological units in developing learners’ linguistic awareness and communicative competence. Special attention is given to the analysis of lexical meanings within different contexts, which enables students to understand polysemy, synonymy, antonymy, and the expressive-stylistic functions of words and idiomatic expressions. The paper highlights the importance of contextual interpretation in revealing the semantic nuances of phraseological units and strengthening students’ ability to use vocabulary appropriately in oral and written speech.
Keywords: Uzbek lexicology; Uzbek phraseology; semantic analysis